A proposed modelling of coupling carbonation-porosity-moisture transfer in concrete based on mass balance equilibrium. (10th January 2020) - Omikrine Metalssi, Othman; Aït-Mokhtar, Abdelkarim; Turcry, Philippe
Highlights: A model of coupled carbonation-moisture transfer is suggested. An experimental validation allows highlighting the role played by moisture transport. The bases of the proposed model make it possible to integrate the hydration process into the coupling. Abstract: This paper deals with modelling the coupled carbonation-porosity-moisture transfer of concrete. A system of mass conservation equations representative of these coupled phenomena has been developed. As a first step of resolution, this system was applied to completely hydrated materials by considering three cases: wetting, drying without moisture exchanges between the material and the external environment during carbonation test. The predicted carbonation depths are deduced and compared with those measured by a phenolphthalein spraying on materials submitted to an accelerated carbonation test. The experimental results and simulations show that the carbonation depths are the highest for the materials equilibrated at low relative humidity (RH = 25%) before carbonation. Besides a faster penetration of CO2 inside the material because of a higher air-volume in the porosity, a convective transport of water vapor occurs at 25% RH from the ambience to the material, which accelerates the progress of the CO2 -RH couple. These results highlight the importance of including moisture transfer when predicting carbonation kinetics in cement-based materials. The basis of the proposed model allows the hydration process to be integrated into the coupling, which would be very useful in the case of cements with additions, which are increasingly used because of their lower environmental impact.